Modification of Extracellular Matrix by the Product of DHA Oxidation Switches Macrophage Adhesion Patterns and Promotes Retention of Macrophages During Chronic Inflammation - Casteel, Jared L.; Keever, Kasey R.; Ardell, Christopher L.; Williams, David L.; Gao, Detao; Podrez, Eugene A.; Byzova, Tatiana V.; Yakubenko, Valentin P. (Frontiers in Immunology, 2022)
Oxidation of polyunsaturated fatty acids contributes to different aspects of the inflammatory response due to the variety of products generated. Specifically, the oxidation of DHA produces the end-product, carboxyethylpyrrole (CEP), that forms a covalent adduct with proteins via an ε-amino group of lysines. Previously, we found that CEP formation is dramatically increased in inflamed tissue and CEP-modified albumin and fibrinogen became ligands for αDβ2 (CD11d/CD18) and αMβ2 (CD11b/CD18) integrins. In this study, we evaluated the effect of extracellular matrix (ECM) modification with CEP on the adhesive properties of M1-polarized macrophages, particularly during chronic inflammation. Using digested atherosclerotic lesions and in vitro oxidation assays, we demonstrated the ability of ECM proteins to form adducts with CEP, particularly, DHA oxidation leads to the formation of CEP adducts with collagen IV and laminin, but not with collagen I. Using integrin αDβ2-transfected HEK293 cells, WT and αD-/- mouse M1-polarized macrophages, we revealed that CEP-modified proteins support stronger cell adhesion and spreading when compared with natural ECM ligands such as collagen IV, laminin, and fibrinogen. Integrin αDβ2 is critical for M1 macrophage adhesion to CEP. Based on biolayer interferometry results, isolated αD I-domain demonstrates markedly higher binding affinity to CEP compared to the “natural” αDβ2 ligand fibrinogen. Finally, the presence of CEP-modified proteins in a 3D fibrin matrix significantly increased M1 macrophage retention. Therefore, CEP modification converts ECM proteins to αDβ2-recognition ligands by changing a positively charged lysine to negatively charged CEP, which increases M1 macrophage adhesion to ECM and promotes macrophage retention during detrimental inflammation, autoimmunity, and chronic inflammation.